PENGELOLAAN DAN MONITORING DATABASED PELANGGAN DENGAN LITERASI FITUR MS. EXCEL PADA UMKM KRIPIK TEMPE SANAN RIZKY BAROKAH DI KOTA MALANG - Sanita Dhakirah; Hilda Cahyani; Isnaini Nur Safitri; Aisyah Vanadia Rubianto; Novitasari (Jurnal Pengabdian kepada Masyarakat, 2023)
In this modern era, doing business requires a marketing strategy to market a product. One good marketing method is to utilize a customer database. A database is a collection of data or information stored systematically. Meanwhile, the customer database is data that contains customer personal information, such as name, email, telephone number, age, gender, product search history, transaction history and other demographic and psychographic data. This database can be used to build and maintain a business, as well as establishing good relationships with customers. As Micro, Small and Medium Enterprises (MSMEs), the hope is that they can keep up with developments by becoming familiar with data. When you are data literate, it will make it easier for MSMEs to develop their business in this digital era. The customer database will help MSMEs reach more consumers. Utilizing data coupled with knowledge in processing customer databases is one of the keys to successfully managing a business. As an MSME actor, you must also be able to use data optimally. The Sanan tempeh chips center, as one of the areas in Malang City, is the center of a home industry that produces tempeh chips that are still surviving in this global era. The aim of this research is to help MSMEs to manage customer databases, business actors know and of course create the best business strategies